KEPEMIMPINAN YANG MENYELAMATKAN: ANALISIS KONSEP KEPEMIMPINAN MONKEY D. LUFFY DALAM ANIME ONE PIECE ARC “MARINEFORD” DAN KONSEP KEPEMIMPINAN YESUS SEBAGAI SAHABAT - Lontoh, Andheralvi Isaiah; Manguju, Yudha Nugraha (SEKOLAH TINGGI TEOLOGI DAN ENTREPRENEURSHIP PRINGGADING (STEP) SEMARANG, 2023)
This article discusses the leadership that has been used by Christianity which is often still not carried out effectively and even provides distance with the existence of a hierarchy. Joas Adiprasetya's Philiarchy leadership and the leadership of Monkey D. Luffy in the